Analisa Teori Post Kolonialisme Dalam Perspektif Alternatif Studi Hubungan Internasional - Artika Diannita (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2021)
Postcolonialism is currently one of the political and theoretical strategies to dismantle Western hegemonies. The focus of this research is an analysis of the post-colonial theory, the views of the figures on the post-colonial theory, how the post-colonial theory is used as an alternative in the study of international relations. The purpose of this study is to analyze how post-colonial theory is, the views of the figures on post-colonial theory, how post-colonial theory is used in the study of international relations, and examples of the application of postcolonial theory in the study of international relations. This writing uses qualitative methods with literature studies using secondary data, using data from books, journals and websites. Postcolonialism theory has an important meaning, it is considered capable of uncovering the hidden problems contained behind the reality that has ever happened. Colonialism uses colonial discourse to amplify the distinction between the colonized and the colonized worlds. They study the colonized people and describe it in various forms of media, writings, films, advertisements, brochures, pictures and other media. The results of this paper examine how the theory of postcolonialism is and how to analyze how the theory of postcolonialism is, the views of the figures on the theory of postcolonialism, how the theory of postcolonialism is used in the study of international relations, and examples of the application of the theory of postcolonialism in the study of international relations